Deep-Drawing Process Simulation for Tailor-Welded Blanks with an Elastic Blankholder - Brusilová, A.; Schrek, A.; Švec, P.; Gábrišová, Z. (Проблемы прочности, 2017)
Application of tailor welded blanks is proved to be very effective in the current trend of body parts construction. However, their formability is limited to the differences of mechanical properties of individual tailor welded blanks parts. These differences result in non-constant material flow and a deflection of the weld line. This article is focused on the elimination of uneven material flow and weld line instability. The results have been obtained by means of laboratory measurements on the drawing tool as well as material simulation computed by LS-DYNA code. According to acquired results, it can be claimed that the blankholder force values and force distribution have a significant influence on the deep-drawing process of tailor welded blanks. The weld line direction in consideration of the blankholder area size has influence on the deflection value. The simulation provided a reliable prediction of tailor-welded blank formability. Показана эффективность использования нестандартных сварных заготовок при проектировании кузовных деталей. Однако их пластичность ограничена из-за разных механических характеристик отдельных деталей из таких заготовок, что приводит к непостоянной текучести материала и перемещению границы сплавления. Проведены лабораторные измерения вытяжки и моделирование материала с использованием программного комплекса LS-DYNA. Показано, что усилие прижима и его распределение существенно влияют на процесс глубокой вытяжки нестандартных сварных заготовок. С учетом размера площади прижима влияние на величину перемещения границы сплавления оказывает ее направление. При прогнозировании пластичности нестандартных сварных заготовок результаты моделирования были весьма надежными.